Chronic oral mucocutaneous candidiasis, recurrent respiratory infection, hepatosplenomegaly, and autoimmune diabetes mellitus: A case report of a gain-of-function mutation of STAT1 in a Chinese boy - Cao, Bingyan; Liu, Meijuan; Zhao, Yun; Gong, Chunxiu (Frontiers in Pediatrics, 2022)
Background: Signal transducer and activator of transcription 1 (STAT1) gain-of-function (GOF) mutations are characterized by chronic mucocutaneous candidiasis and autoimmune diseases. Type 1 diabetes mellitus (TIDM) is one of the well-characterized autoimmune conditions. Case presentation: We reported a 5-year-old boy who presented with polydipsia and polyuria, with a medical history of chronic oral mucocutaneous candidiasis, recurrent respiratory infection, hepatosplenomegaly, and abnormal liver function. Genetic analysis identified a heterozygous GOF mutation (c.866A>G, p.Y289C) in STAT1. Results: Various medicines were given to the boy during the follow-up, including insulin to keep blood glucose stable, intravenous immunoglobulin and antifungal agents for recurrent infections, and antituberculosis drugs (Isoniazid, Rifampicin) to combat tuberculosis infection. He did not show recurrent infection, but chronic oral mucocutaneous candidiasis still occurred twice per month. The blood glucose level was well controlled. Conclusion: This article illustrates that early diagnosis and identification of STAT1 mutation are essential for assessing the severity of the disease and determining reasonable treatment options.